Research on the STATCOM Mathematical Model of Battery Storage in HVDC Transmission System - Xing, Chao; Chen, Junhao; Xi, Xinze; Xu, Zhi; He, Xin; Li, Shengnan; Chen, Shilong (Frontiers in Energy Research, 2022)
When traditional STATCOM (Static Synchronous Compensator) performs large-capacity reactive power compensation, the control accuracy of the DC side voltage will be affected and the DC side voltage will fluctuate greatly. Therefore, this study proposes to use battery energy storage STATCOM (STATCOM/BESS) and gives the main circuit topology of STATCOM/BESS. By analyzing the working principle of STATCOM/BESS, the mathematical model and control method are derived and modeled, in which the Shepherd model is used as the energy storage battery in STATCOM/BESS. Aiming at the possible imbalance of the battery state of charge (SOC) in STATCOM/BESS, the phase-to-phase SOC balance control and phase control are proposed. At last, in PSCAD/EMTDC simulation software, STATCOM/BESS is tested for dynamic response and steady-state response performance of active power control, reactive power control, and transformation failure suppression test, which verifies the effectiveness and superiority of STATCOM/BESS commutation failure.